2020
DOI: 10.3390/resources9120143
|View full text |Cite
|
Sign up to set email alerts
|

Suitability of Wild Phragmites australis as Bio-Resource: Tissue Quality and Morphology of Populations from Three Continents

Abstract: We collected and analyzed morphological characteristics and tissue nutrient concentrations of common reed (Phragmites australis) populations from Denmark, USA, and China, harvested late summer at the peak of the biomass production. The aim was to estimate the suitability of the biomass for different bioenergy purposes. The potential of reed as bioenergy feedstock is increasingly recognized, as the species already is utilized for construction, water purification, and pulp production. Our morphological data show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 66 publications
0
5
0
Order By: Relevance
“…Another perennial grass, D. bipinnata , is composed of 26.67% cellulose, 24.68% hemicellulose, 12.87% ash, and 6.67% lignin ( Shah et al, 2017 ; Munir et al, 2020 ), is considered as sacred in India, and has been extensively studied for the isolation of medicinally important compounds and for pharmacological properties ( Guntur et al, 2018 ). P. karka is reported as the herbaceous woody culms that range from 4 to 10 m in length and 15–25 mm in diameter and is composed of 26% cellulose, 29% hemicellulose, and 10.33% lignin ( Munir et al, 2020 ) and 3.9–8.5% ash ( Eller et al, 2020 ). Moreover, it can tolerate high ranges of salinity and flooding stress with enhanced growth rates ( Shoukat et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Another perennial grass, D. bipinnata , is composed of 26.67% cellulose, 24.68% hemicellulose, 12.87% ash, and 6.67% lignin ( Shah et al, 2017 ; Munir et al, 2020 ), is considered as sacred in India, and has been extensively studied for the isolation of medicinally important compounds and for pharmacological properties ( Guntur et al, 2018 ). P. karka is reported as the herbaceous woody culms that range from 4 to 10 m in length and 15–25 mm in diameter and is composed of 26% cellulose, 29% hemicellulose, and 10.33% lignin ( Munir et al, 2020 ) and 3.9–8.5% ash ( Eller et al, 2020 ). Moreover, it can tolerate high ranges of salinity and flooding stress with enhanced growth rates ( Shoukat et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…The reed roots extend up to approximately 95 cm in the soil, where the water and nutrient requirements are ensured, and the extensive network of rhizomes ensures the storage of substances in the cold season and the asexual growth of the plant even if the above-ground stems are cut [ 28 30 ].…”
Section: Resultsmentioning
confidence: 99%
“…P. australis is an essential native species, highly adaptable to various environments in coastal wetland ecosystems. P. australis absorbs nutrients and heavy metals, builds and stabilizes soil, and creates self-sustaining vegetation in urban and industrial areas where many other plants do not flourish ( Eller et al., 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies suggested that identifying and selecting foundation species is a key step in ecosystem restoration ( Ellison et al., 2019 ), necessitating an urgent understanding of enhanced ecosystem services following the planting and establishing of the foundation species ( Angelini et al., 2011 ; Osland et al., 2014 ). As one of the primary species, Phragmites australis (common reed) dominates the ecological community engineering effect in biomass and spontaneous ecosystems ( Eller et al., 2020 ) and has a forward-looking ecological theoretical guidance ( Crain and Bertness, 2006 ; Bonanno and Lo Giudice, 2010 ) and restoration practice ( Hastings et al., 2007 ). The spatial structure of P. australis genotypes under changing environments is linked to patch habitats.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation